Peran Pembinaan Warga Jemaat Dalam Menghadapi Fenomena Kekerasan Dalam Pacaran Pada Remaja - Mariani Harmadi; Ruat Diana (Integritas: Jurnal Teologi, 2020)
Violence in courtship is a problem that requires handling from various parties, both partially and structured. The author uses a literature study approach to examine this issue. In this study emphasizes that there is a role for the church in providing guidance to adolescents to reduce the occurrence of violence in courtship. The church needs to provide a forum within the framework of fostering members of the congregation to minimize the occurrence of dating violence.